The Role of Islamic Religious Education Teachers in Instilling Religious Tolerance Values in Schools - Miftahul Jannah (Indonesian Journal for Islamic Studies, 2025)
This study aims to examine the role of Islamic Religious Education teachers in instilling the values of religious tolerance in schools. Using qualitative methods and descriptive approaches, data were obtained through in-depth interviews, classroom observations, and analysis of related documents. The results showed that Islamic Religious Education teachers play a crucial role as models and facilitators in instilling the value of tolerance through dialogic learning, interfaith activities, and integration of these values in the curriculum. The challenges faced include time constraints, student resistance, and the influence of the external environment. However, in general, students showed positive responses and there was increased interaction between students of different religions, creating a more inclusive school environment.  This study concludes that the role of Islamic Religious Education teachers is crucial in shaping attitudes of religious tolerance among students and further policy support and teacher training are needed to overcome the challenges and strengthen the inculcation of religious moderation in schools.